The Relationship between Maternal Health Literacy and Nutritional Dietary Self-Efficacy with Pregnancy Outcome - Seyede Sara kharazi; Nooshin Peyman; Habibolah Esmaily (Mashhad University of Medical Sciences, 2020)
Background & aim: The investigation and identification of health predictive factors in promoting healthy behaviors of women at reproductive age can improve maternal health and pregnancy outcomes. This study aimed to determine the relationship between maternal health literacy and dietary self-efficacy and its impact on pregnancy outcomes and neonatal birth weight. Methods: This descriptive-analytical cross-sectional study was conducted on 120 pregnant women referred to health care centers of Mashhad University of Medical Sciences in 2016. The study population was selected using multistage sampling method. The data were collected utilizing Maternal Health Literacy and Pregnancy Outcome Questionnaire, Perceived Dietary Self-Efficacy, Perceived Nutritional Status and Dietary Behavior Questionnaire after the confirming validity and reliability. Data was analyzed in SPSS software (version 15) and descriptive-analytic tests, namely Pearson's correlation coefficient, Stepwise regression method, independent t-test, one-way analysis of variance, as well as Tukey's range test, with the significant level of 95% and 99%. Results: Perceived nutritional status (r=0.585, P<0.01), nutritional self-efficacy (P<0.01, r=0.711), dietary behavior (P<0.01, r=0.682), and health literacy (P<0.01, r=0.679) had a positive and significant correlation with the pregnancy outcomes and neonatal birth weight. The results of stepwise regression analysis showed that, dietary self-efficacy (R=0.71), health literacy (R=0.76), and dietary behaviors (R=0.77) could significantly predict pregnancy outcomes in the first, second, and third steps, respectively. Totally, these variables could anticipate 59% of the pregnancy outcome variance (P<0.01). Conclusion: Maternal health literacy and dietary self-efficacy in pregnant women played an important role in the prediction of pregnancy outcomes and neonatal birth weight.